Production of biodiesel from waste cooking oil using bentonite catalysts / Noraini Hamzah ... [et al.] - Hamzah, Noraini; Yusof, Izyan; Samad, Wan Zurina; Saleh, Sabiha Hanim; Ahmad Tajuddin, Nazrizawati; Ibrahim, Mohd Lokman (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Demand for diesel continues to increase due to rapid population growth, which could contribute to fossil fuel exhaustion. Biodiesel has been widely developed as a replacement for conventional diesel to resolve the issue. Biodiesel production from waste cooking oil (WCO) was carried out via the transesterification process using two types of bentonite catalysts, which are raw bentonite and NaOH/bentonite. By using the impregnation method, the NaOH/bentonite catalyst was synthesized at 60°C for 12 hours. The transesterification was conducted with 0.5wt% of catalyst, at 15:1 (methanolto-oil), for 2 hours at different reaction temperatures. The characterization of both raw bentonite and NaOH/bentonite was done using X-ray Diffraction (XRD) and Brunauer, Emmett, Teller (BET) surface characterization. A high yield of FAMEs (72%) was found to be obtained in continuous stirring at 55ºC for 2 hours and 15:1 methanol/oil molar ratio with 0.5wt.% (0.15g) of NaOH/bentonite catalyst.